AI-based prediction of pulmonary hypertension in COPD patients with cor pulmonale using clinical and CT features - Xiaohui Tan; Mian Luo; Rui Ma; Huanchi Liu; Lihua Xie; Rongchang Zhao (Frontiers in Medicine, 2026)
Background and objectives This study aimed to characterize COPD with clinically defined cor pulmonale and to develop clinical and contrast-enhanced CT-based AI-assisted models for its identification. Methods We retrospectively enrolled 179 patients with COPD (90 COPD alone and 89 COPD with cor pulmonale). Clinical, laboratory, pulmonary function, electrocardiographic, and echocardiographic data were compared. To reduce incorporation bias, right ventricular, right atrial, and pulmonary artery measurements and electrocardiographic variables used in the operational case definition were excluded from candidate predictors. Variables associated with cor pulmonale in univariable analysis were entered simultaneously into multivariable logistic regression. A conservative sensitivity analysis additionally excluded mMRC score because dyspnea contributed to clinical case ascertainment. In 63 patients with diagnostic-quality CT angiography, pulmonary artery volumes were quantified using a U-Net model. Results In the revised multivariable clinical model ( n = 177), acute exacerbations in the past year (adjusted OR, 3.532; 95% CI, 1.893–6.593) and mMRC score (adjusted OR, 2.165; 95% CI, 1.363–3.439) were positively associated with cor pulmonale. Hypertension showed an inverse sample-specific association (adjusted OR, 0.333; 95% CI, 0.141–0.784). The revised model achieved an AUC of 0.888 (95% CI, 0.838–0.937), with 79.3% sensitivity and 87.8% specificity. The sensitivity model excluding mMRC score retained an AUC of 0.870 (95% CI, 0.816–0.923). The small pulmonary artery volumes Vd 12 , Vd 20 , Vs 15 , and Vs 30 mm were lower in the cor pulmonale group as reported in the vascular analysis, and the AI-assisted vascular model yielded an AUC of 0.895 (95% CI, 0.820–0.970). Conclusion A revised clinical model that excluded variables incorporated into the diagnostic definition retained good discrimination for clinically defined cor pulmonale. AI-assisted quantification of small pulmonary vessels may provide complementary non-invasive information.